Longitudinal Analysis of Psychosocial Stressors and Body Mass Index in Middle-Aged and Older Adults in the United States. (28th August 2020) - Cuevas, Adolfo G; Greatorex-Voith, Siobhan; Assari, Shervin; Slopen, Natalie; Economos, Christina D
Abstract: Objectives: Psychosocial stress may be a risk factor for obesity and overweight in middle-aged and older adults. However, research on psychosocial stress and excess body weight has typically been cross-sectional and focused on single stressors. Methods: Using 3 waves of data from the Health and Retirement Study, we conducted longitudinal analyses to assess associations between 5 psychosocial stressors—individually and in combination—and body mass index (BMI), adjusting for sociodemographic factors, alcohol use, and smoking history. We tested interaction effects between race and gender with stressors on BMI. Results: A total of 3, 956 participants were included in the main analyses. Most participants were White (88.04%) and more than half were female (60.39%). Perceived discrimination, financial stress, and relationship stress were positively associated with BMI. A greater cumulative stress burden was associated with higher BMI. In stratified analyses, greater financial stress was associated with higher BMI among White participants, whereas greater neighborhood stress was associated with lower BMI among Black participants. Greater relationship stress, financial stress, cumulative high stress, and overall cumulative stress burden were associated with higher BMI for women, but not men. Discussion: Different sources of stress may be risk factors to weight gain and affect BMI in adults. White and female adults may be more susceptible to the obesogenic effects of stressors. Reducing exposure to stress may help reduce the burden of high BMI among middle-aged and older adults.